2000
DOI: 10.1176/appi.ajp.157.6.924
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gonadal Steroids in Women With a History of Postpartum Depression

Abstract: The data provide direct evidence in support of the involvement of the reproductive hormones estrogen and progesterone in the development of postpartum depression in a subgroup of women. Further, they suggest that women with a history of postpartum depression are differentially sensitive to mood-destabilizing effects of gonadal steroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
485
1
21

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 782 publications
(528 citation statements)
references
References 26 publications
21
485
1
21
Order By: Relevance
“…In order to test whether the change in hormone levels is indeed responsible for postpartum depression, one study treated females with the very high levels of estrogen associated with pregnancy followed by treatment with low levels associated with postpartum. Females either had a history of postpartum depression or did not (Bloch et al, 2000). As expected, treated females with a history developed dysphoric mood consistent with depression whereas those treated without a history did not.…”
Section: Female Depression and The Role Of Ovarian Hormonessupporting
confidence: 57%
“…In order to test whether the change in hormone levels is indeed responsible for postpartum depression, one study treated females with the very high levels of estrogen associated with pregnancy followed by treatment with low levels associated with postpartum. Females either had a history of postpartum depression or did not (Bloch et al, 2000). As expected, treated females with a history developed dysphoric mood consistent with depression whereas those treated without a history did not.…”
Section: Female Depression and The Role Of Ovarian Hormonessupporting
confidence: 57%
“…A pharmacological model of PPD supports this hypothesis; simulating the postpartum state by administrating pregnancy levels of gonadal steroids and rapidly withdrawing them significantly increases the incidence of depression in women with a history of PPD more than in nondepressed women. Although statistically not significant, the scores of depression scales are higher in the withdrawal period in nonde-pressed women, indicating that these endocrine events provoke mood changes in postpartum women (6). However, the underlying neurobiological mechanisms that contribute to PPD have not been determined.…”
mentioning
confidence: 87%
“…First, as reviewed above, allopregnanolone negatively modulates the HPA axis in animal models, and although null findings have been reported (Su et al, 1997;Bloch et al, 2000;Lombardi et al, 2004) where diagnosis-related differences exist, they suggest blunted HPA axis function in PMDD. For example, a number of studies have reported lower circulating ACTH or cortisol concentrations in PMDD women (Rabin et al, 1990;Redei & Freeman, 1993;Girdler et al, 1998), increased ACTH response to ovine CRF (consistent with lower endogenous CRF; Rabin et al, 1990), a delayed (Steiner et al, 1999) or blunted HPA axis response to serotonergic agents (Bancroft et al, 1991;Su et al, 1997), and the absence of the normal plasma cortisol and ACTH response to exercise stress in the luteal phase that is seen in non-PMDD women (Roca et al, 2003).…”
Section: Hpa Axis and Gaba A Receptor Function In Pmddmentioning
confidence: 99%
“…Histories of depression, which are more prevalent in PMDD women (Cohen et al, 2002), may provide a context of vulnerability for the dysphoric effects associated with steroid hormones (Rubinow, 2005). For example, Bloch et al (2000) demonstrated that euthymic women with a past history of postpartum depression experienced significant depression when exposed to high doses of hormone add-back and withdrawal, effects not seen in women with no prior history of depression. Divergent evidence suggests that in euthymic women, histories of depression are associated with persistent disturbance in HPA axis function (Young et al, 2000a(Young et al, , 2000b as well as thyroid axis function relative to never-depressed women.…”
Section: Histories Of Depression and Allopregnanolone Stress Responsimentioning
confidence: 99%